Studies on Germination of Neem (Azadirachta indica A.juss.) Seeds at Different Temperature and Substrates - Shringirishi, Nikhil; , Narendra; Shukla, K.; Srivastava, Ram Jee; Dubey, P. (Indian Forester, 2001)
Laboratory studies were conducted to determine the,effect of different temperatures and subtrates for germination of Neem (Azadirachta indica, A. Juss.) seeds. These two factors significantly influenced the germination of this species. Among all the combinations of test the maximum germination per cent and Mean Daily Germination (MDG) was obtained at 30°C, on top of the paper (TP) in 24 days. The 30°C on between the paper was also found to be equally effective for germination per cent and MDG of seeds. Temperature 20°C was not favourable for germination in comparison to other temperatures and substrates.